PENDIDIKAN BUDI PEKERTI PADA CERITA SANG GARUDA DALAM TEKS ĀDIPARWA - Ni Nengah Sudarsini (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
The values ​​of manners education when associated with the teachings of Hinduism contain a lot of education about ethics, morals, and character. In the story Adiparwa is one of the sub Mahabharata, one of which tells of the birth of the Garuda, the son of the goddess Winata who is full of manners education values ​​that can be used as guidelines for students. The writing method in question is related to data discovery and data analysis. In finding the data, a literature study method was used which was carried out by searching for literature containing the story of the Garuda. Especially in the story of Adiparwa, there is an interesting part of the story of Sang Garuda. Through this literature study, a narrative story about the Garuda is obtained. Through this literature search, characters and characters in the story of the Garuda are also obtained. Based on the research conducted, in this study found the value of manners education which is reflected in the story as follows: honest, disciplined, hard work, creative, independent, democratic, peace-loving